Podocalyxin Expressed in Antigen Presenting Cells Promotes Interaction With T Cells and Alters Centrosome Translocation to the Contact Site - Amo, Laura; Díez-García, Javier; Tamayo-Orbegozo, Estíbaliz; Maruri, Natalia; Larrucea, Susana (Frontiers in Immunology, 2022)
Podocalyxin (PODXL), a cell surface sialomucin expressed in diverse types of normal and malignant cells, mediates cellular adhesion to extracellular matrix and cell-to-cell interaction. A previous study reported the expression of PODXL protein on monocytes undergoing macrophage differentiation, yet the expression of this molecule in other antigen presenting cells (APCs) and its function in the immune system still remain undetermined. In this study, we report that PODXL is expressed in human monocyte-derived immature dendritic cells at both the mRNA and protein levels (DCs). Following DC maturation using pro-inflammatory stimuli, PODXL expression level decreased substantially. Furthermore, we found that PODXL expression is positively regulated by IL-4 through MEK/ERK and JAK3/STAT6 signaling pathways. Our results revealed a polarized distribution of PODXL during the interaction of APCs with CD4+ T cells, partially colocalizing with F-actin. Notably, PODXL overexpression in APCs promoted their interaction with CD4+ T cells and CD8+ T cells and decreased the expression of MHC-I, MHC-II, and the costimulatory molecule CD86. In addition, PODXL reduces the translocation of CD4+ T-cell centrosome toward the APC-contact site. These findings suggest a regulatory role for PODXL expressed by APCs in immune responses, thus representing a potential target for therapeutic blockade in infection and cancer.